Avaliação da bergenina em modelos experimentais in vitro relacionados a doenças metabólicas - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Changes in the global economy have contributed to a sedentary lifestyle and excessive intake of calories, increasing the incidence of metabolic disease, and have become a global public heath problem. It is estimated that these numbers will continue to increase by 25% through 2030 and 51% into 2045. Regarding available tratments for metabolic diseases, there are few therapeutic options to date, and existing therapies are limite dor have side effects. The use of natural product in metabolic diseases has shown positive results. Recent research demonstrates that bergenin has a wide range of pharmacological effects on oxidative and anti-inflammatory stress, making it a Strong candidate for treatments for these diseases. Thus, this work aimed to evaluate the possible therapeutic effects of bergenin in models of metabolic disease by in vitro experimental procedures. The bergenin used in the study was obtained commercially and evaluated for its chemical nature and purity. Antoxidant activity through DPPH radical scavenging activity and ABTS radical scanning assay, where it was observed that bergenin has greater activity on ABTS radicals. Bergenin was evaluated for is potential to inhibit protein glycation by the oxidative and non-oxidative pathways, showing a moderate effect of activity on the oxidative pathway. The effect on tumor anda non-tumor cell viability when in contact with bergenin was analyzed using the resazurina method (Alamar blue). The bergenin was not toxic to MRC-5 and HepG2 strains up to the concentration of 200 µM. The cell antioxidant test was perfomed using 2’7-dichlorofluorescein-diacetate (DCFH-DA), where bergenin inhibited in a concentration-dependent manner about 30% of the reactive oxygen species generated. This study showed for the first time that bergenin has the potential to inhibits the α-amylase enzyme. The lipid uptake assay was performed by the Oil Red O method and the results of the inhibition of lipid uptake by bergenin were not significant. Given these results, it is understood that bergenin has the potential to be better studies as a therapeutic option in metabolic diseases. However, additional in vivo studies are needed to better elucidate the possible pharmacological effects of bergenin in chronic disease.
Keywords: Distúrbios do metabolismo; Agentes antiinflamatórios; Produtos naturais; CIENCIAS DA SAUDE; Bergenina; Doença metabólica; Atividade farmacológica; Atividade anti-inflamatória; Antioxidante